Fast growth of single-crystal covalent organic frameworks for laboratory x-ray diffraction - Han, Jing; Feng, Jie; Kang, Jia; Chen, Jie-Min; Du, Xin-Yu; Ding, San-Yuan; Liang, Lin; Wang, Wei (Science (American Association for the Advancement of Science), 2024)
The imine-exchange strategy makes single-crystal growth of covalent organic frameworks (COFs) with large size (>15 microns) possible but is a time-consuming process (15 to 80 days) that has had limited success (six examples) and restricts structural characterization to synchrotron-radiation sources for x-ray diffraction studies. We developed a CF 3 COOH/CF 3 CH 2 NH 2 protocol to harvest single-crystal COFs within 1 to 2 days with crystal sizes of up to 150 microns. The generality was exemplified by the feasible growth of 16 high-quality single-crystal COFs that were structurally determined by laboratory single-crystal x-ray diffraction with resolutions of up to 0.79 angstroms. The structures obtained included uncommon interpenetration of networks, and the details of the structural evolution of conformational isomers and host-guest interaction could be determined at the atomic level. The production of large crystals of porous covalent organic frameworks (COFs) usually requires slow growth over weeks to avoid precursor assembly that results in defects. Han et al . found that large imine-linked single-crystal COFs (15 to 100 micrometers) can be grown in 1 or 2 days using trifluoroacetic acid as a catalyst and trifluoroethylamine as an intermediate reactant that is displaced by the reactant amine. This approach grew a wide variety of large COF crystals with x-ray diffraction resolutions up to 0.8 angstroms. —Phil Szuromi A modulator-catalyst protocol enabled growth of large-sized single-crystal covalent organic frameworks within 1 to 2 days.